Understanding the Determinants of Continuance Intention for Banking Chatbots: A TCT Study - Wirapraditya Ramdhani, Angga; Fangdinata, Felicia; Mandoyo, Joko (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2025)
The banking industry has witnessed tremendous changes in its structure within a short time frame due to scientific strides and the AI sector took it one step further, chatbots became an innovative trend. This research is to investigate the factors which may help determine continuance intention for banking chatbots in Indonesia using Technology Continuance Theory (TCT). The goal of this research is to close the knowledge gap regarding what motivates customers in continuous utilization after an initial adoption. This study carries out a survey of 153 bank customers and employs the Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique to examine relationships among perceived usefulness, perceived ease of use, service quality, satisfactions, trust, confirmation of expectations on continuance intention. The findings reveal that these factors significantly influence the continuance intention of customers, providing valuable insights for banks to enhance their chatbot services and ensure sustained user engagement.